Healthcare knowledge sharing among a community of specialized physicians - Sabeeh, Z.; Syed Mustapha, S.M.F.D; Mohamad,, R. (2018)
Healthcare organizations strive to make the best use of their organizational knowledge. The collective know-hows of the medical workers directly affect the quality of the delivered healthcare services. This study addresses the healthcare knowledge-sharing among a community of specialized physicians. An extensive study of the literature on knowledge-sharing in industries generally and healthcare organizations specifically were presented. Six focal elements were detected in previous attempts to address the knowledge-sharing status in healthcare organizations. Additionally, three previous models for healthcare knowledge management were analyzed. The studied literature along with the three studied models helped in constructing the framework and suggesting a suitable research methodology for primary data collection. Qualitative approach of in-depth interview technique was used for interviewing eight specialized physicians. The data collected from the interviewees were then analyzed and produced explanatory themes and codes. These themes are physicians’ acquisition of medical knowledge, staff participating in the knowledge sharing, knowledge-sharing culture, ICT-based knowledge sharing and top management involvement. The findings resulted in recognizing four considerations which ought to be taken into account for successful knowledge-sharing activities and learning initiatives in the healthcare organization. Conclusions and recommendations for future studies were presented based on the implications of this research study.